2007
DOI: 10.1016/j.pain.2006.09.003
|View full text |Cite
|
Sign up to set email alerts
|

NMDA receptor-independent synaptic plasticity in the central amygdala in the rat model of neuropathic pain

Abstract: Neurons in the latero-capsular part of the central nucleus of the amygdala (CeA), a region now called the "nociceptive amygdala", receive predominantly nociceptive information from the dorsal horn through afferent pathways relayed at the nucleus parabrachialis (PB). Excitatory synaptic transmission between the PB afferents and these neurons is reported to become potentiated within a few hours of the establishment of arthritic or visceral pain, making it a possible mechanism linking chronic pain and unpleasant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
211
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 206 publications
(233 citation statements)
references
References 44 publications
14
211
1
1
Order By: Relevance
“…It is also important to consider that mGluR7 and mGluR8 may play different roles in more chronic pain states, because mechanisms of amygdala plasticity in acute and chronic pain models appear to be different (Ikeda et al, 2007;Neugebauer, 2007b). On the other hand, enhanced glutamatergic transmission is a key mechanism of amygdala plasticity in the acute (Bird et al, 2005; as well as the chronic pain model (Ikeda et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to consider that mGluR7 and mGluR8 may play different roles in more chronic pain states, because mechanisms of amygdala plasticity in acute and chronic pain models appear to be different (Ikeda et al, 2007;Neugebauer, 2007b). On the other hand, enhanced glutamatergic transmission is a key mechanism of amygdala plasticity in the acute (Bird et al, 2005; as well as the chronic pain model (Ikeda et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In support of this argument, in vivo blockade of synaptic potentiation with intra-amygdaloid infusion of U0126 reduces behavior sensitization in mice with AIMP. This LTP-like enhancement might also account for the increased non-NMDAR-mediated currents at PBA-CeAC synapses seen in an arthritic pain model (Ikeda et al, 2007).…”
Section: Nmdar-pkc-erk-dependent Ltp Of Pba-ceac Synaptic Transmissionmentioning
confidence: 91%
“…Furthermore, the potentiation of the aEPSC amplitude by PDA application was occluded in slices from AIMP mice. Accordingly, we propose that, in AIMP mice, an excessive nociceptive signal triggered by acidic saline injection into the gastrocnemius muscle activates ERK in the central amygdala, thereby enhancing PBA-CeAC synaptic transmission [see also Neugebauer et al (2003Neugebauer et al ( , 2004 and Ikeda et al (2007)]. Although the observation of increased pERK levels in the CeAC is consistent with previous studies, there is a substantial difference between the results of the present study and those of previous studies, in which mechanical hypersensitivity was shown to be functionally lateralized to the right amygdala in intraplantar formalin and arthritic models (Carrasquillo and Gereau, 2008;Ji and Neugebauer, 2009;Kolber et al, 2010).…”
Section: Pda Induces Potentiation Of Pba-ceac Synaptic Transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supraspinal mechanisms: Contralateral effects may be mediated by brain activation and descending facilitation in chronic pain state. Persistent noxious inputs from the periphery may sensitize certain brain areas involved in the central pain circuitry, such as ACC, IC and amygdala (Ikeda et al, 2007) (for review, see Meeus & Nijs, 2007). Activation of these areas may cause bilateral hyperalgesia via descending pain control system (Fig.…”
Section: A Unilateral Nerve Injury-induced Bilateral Hyperalgesiamentioning
confidence: 99%